The influence of earthquake vertical component on the seismic response of masonry structures. (15th April 2019) - Rinaldin, Giovanni; Fasan, Marco; Noé, Salvatore; Amadio, Claudio
Highlights: The effects of the vertical component of an earthquake on URM buildings are investigated. Considerations on common capacity models used in seismic design are provided. A simple façade has been analysed to evaluate the demand/capacity ratios. Such ratios have been collected with and without the vertical component. Abstract: The seismic behaviour of masonry structures is, as well-known, strongly influenced by axial stresses. During a seismic event, variations in axial loading cause in fact a change, that can be substantial, in the response in the lateral resistance capacity of masonry panels. Moreover, the axial stress can be modified by the vertical component of the seismic input during an event, which can amplify the strength variations, in particular if there is a near-fault excitation. In general, such vertical component is neglected in a traditional design. In this work, the influence of the vertical component of a seismic event is evaluated by measuring the lateral resistance of masonry piers. Such influence is estimated through a cyclic phenomenological model which calculates in an analytical way the lateral strength of a masonry panel on the base of the actual axial loading, reached step-by-step during a non-linear analysis. This model is used to simulate the cyclic behaviour of an unreinforced masonry façade made of 3 piers, having the same section for 2 floors and connected by rigid spandrels. The wall, representative of a typical masonry façade, is subjected to a series of earthquake records, with and without the vertical component of the seismic input. The differences in the responses are quantified through the use of seismic reduction factors, in such a way to satisfy the checking of the piers adopting the current design codes.